الكفاءة الذاتية لدى طلبة المرحلة الاعدادية (Journal of the College of Basic Education, 2026)
The current ressarch aims to identify: 1-The level of Self Efficacy among secondary school students 2-The level of Self Efficacy among secondary school student according to gender variable (males-females) 3-The level of Self Efficacy among secondary school student according to the specialization variable (literary-scientific) The current research community consists of secondary school students the academic year2024/2023 . The research sample was (300) from high school students. In order to achieve the research objectives of the Self Efficacy, the research. And the scale became in its final form (36) paragraphs.The researcher used statistical methods (t-test for one sample, t-test for two different samples, Pearson and Wackronbach correlation coefficient). The researcher reached the following results:- 1- The secondary school students have an average level of in Self Efficacy analytics.2ـ There are statistically diff Self Efficacy in the I, according to the change of sex, (males – females), in favor of females.3ـ There are no Self Efficacy differences in the according to the change of specialization, (literary – scientific). In light of the results reached, the researcher formulated a number of recommendations and proposals